Antibacterial Activity of Eichornia crassipes Leaf and Eggshell Extracts Against Staphylococcus aureus and Staphylococcus mutans - Nugrahani, Baiq Dwiyan; Habibie, Irhas Anugrahadi; Ramadhan, Muhammad Rafi Bintang; Pitaloka, Galuh Suli; Rismawati, Dhity; Hajrin, Wahida (Jurnal Biologi Tropis, 2025)
Dental disease remains a major health concern in Indonesia, with a high prevalence across various age groups. This study aims to formulate and evaluate herbal toothpaste using Eichhornia crassipes (water hyacinth) leaf extract and eggshell powder, and to determine its antibacterial activity against Streptococcus mutans and Staphylococcus aureus. The toothpaste was prepared in three formulations with varying concentrations, followed by evaluation of its physical properties and antibacterial activity using the well diffusion method. Among the formulations, F1 containing 3% water hyacinth extract and 15 g eggshell powder showed optimal results. F1 fulfilled physical quality standards based on SNI 12-3524-1995, including pH, viscosity, and foam formation. Antibacterial testing demonstrated that F1 exhibited very strong inhibition zones of 21.87 mm against S. aureus and 21.50 mm against S. mutans. These findings indicate that a combination of water hyacinth extract and eggshell powder is effective as an active agent in herbal toothpaste. This research supports the utilization of abundant local waste materials as a sustainable alternative in oral health care formulations.